Effects of an ad valorem Web Tax in a Cournot-Nash market for digital advertising - Diego d'Andria (European Commission, Joint Research Centre (JRC), 2018)
We extend the theory of tax incidence under Cournot-Nash oligopolistic competition to study the effects of an ad valorem sales tax on Web services (so-called Web Tax) that are provided free of charge to users, and produce advertising space sold to businesses. Ads are more valuable to advertisers the more users are served by a Web service. Users have ads-neutral preferences and Web companies compete in a Cournot-Nash fashion on the advertising market but enjoy monopolistic power in the service market they serve. We demonstrate that, contrary to standard theoretical results, the equilibrium market price might be reduced by a Web Tax. The conditions for such a decrease depend upon the elasticity of ads demand.
Keywords: D43; H2; L13; 330; Web tax; digital advertising; Cournot competition; tax incidenceâ exteuro